Cell wall modifications by α-XYLOSIDASE1 are required for control of seed and fruit size in Arabidopsis. (25th November 2021) - Di Marzo, Maurizio; Viana, Vívian Ebeling; Banfi, Camilla; Cassina, Valeria; Corti, Roberta; Herrera-Ubaldo, Humberto; Babolin, Nicola; Guazzotti, Andrea; Kiegle, Edward; Gregis, Veronica; de Folter, Stefan; Sampedro, Javier; et al.
Abstract : Cell wall modifications induced by α-XYLOSIDASE1, which is regulated by the transcription factor SEEDSTICK, determine seed and fruit size. Abstract: Cell wall modifications are of pivotal importance during plant development. Among cell wall components, xyloglucans are the major hemicellulose polysaccharide in primary cell walls of dicots and non-graminaceous monocots. They can connect the cellulose microfibril surface to affect cell wall mechanical properties. Changes in xyloglucan structure are known to play an important role in regulating cell growth. Therefore, the degradation of xyloglucan is an important modification that alters the cell wall. The α - XYLOSIDASE1 ( XYL1 ) gene encodes the only α-xylosidase acting on xyloglucans in Arabidopsis thaliana . Here, we showed that mutation of XYL1 strongly influences seed size, seed germination, and fruit elongation. We found that the expression of XYL1 is directly regulated in developing seeds and fruit by the MADS-box transcription factor SEEDSTICK. We demonstrated that XYL1 complements the stk smaller seed phenotype. Finally, by atomic force microscopy, we investigated the role of XYL1 activity in maintaining cell stiffness and growth, confirming the importance of cell wall modulation in shaping organs.